(untitled) (International Journal of Scientific Trends, 2024)
The present article is concerned with the developing of slangs and different approaches to types of slang in English. Furthermore, it deals with the development of active term “slang” in sociolect by young generation. The role and function of Youth slang are given in social layer within comparing world linguistic views on the types of slang. As Youth slang is commonly used and created by young people in Uzbek, it is considered to be a dominant factor inside of Slang itself.